PENGARUH SARANA WISATA TERHADAP KEPUASAN WISATAWAN DI PANORAMA TABEK PATAH KABUPATEN TANAH DATAR - Dewi, Susi Safra; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aimed to determine the influence of tourism facilities toward the tourists satisfaction at Panorama Tabek Patah Kabupaten Tanah Datar. The type of this research was associative causal. The population in this research was the average of the tourists about 1,001 persons each month. The technique of sampling was non-probability sampling (purposive sampling). The number of samples in this research were 91 persons by using the Riduwans’ formula. The technique of data collecting by using a questionnaire based on Likert Scale which has proven its validity and reliability. Generally, tourism facilites was bad about 48,35% and the tourists satisfaction was good enough about 67,03%. Then, the result of regression linier obtained F count with sig . 0.000 < 0.05. From the hypotesis test, the result of R Square was 0.600. This means that tourism facilities influenced tourists satisfaction about 60%, while the remainder influenced by other factors.Keywords : tourism facilities, tourists satisfaction